Chitty Chitty Bang Bang flies again - Cottrell Boyce, Frank. (Candlewick Press, 2012)
Down on their luck, the Tooting family buys an old camper van and begins repairing it, but after installing an engine that once belonged to an extraordinary car, they are off to find other original parts, pursued by a sinister man who wants Chitty for himself.